2021
DOI: 10.1111/ejn.15319
|View full text |Cite
|
Sign up to set email alerts
|

Participation of glutamatergic and nitrergic systems in the striatal dopamine release induced by isatin, a MAO inhibitor

Abstract: Isatin is a biofactor with different biochemical and pharmacological properties whose effects attract much attention because it is an endogenous inhibitor of the monoamine oxidase in the brain. When exogenously administrated, isatin increases dopamine levels in intact and denervated striatum of rats, an effect that could indicate its potential as a therapeutic agent in Parkinson disease. However, the neurochemical mechanisms by which isatin increases dopamine in the striatum are poorly understood. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The authors suggested in agreement with others, that isatin may increase dopamine levels through greater availability of dopamine in the cytoplasmic reservoir ( Butcher et al, 1988 ; Justo et al, 2016 ). Isatin was further investigated by Faro et al (2021) who found that this MAO-inhibitor likely increases dopamine availability through a) suppression of dopamine metabolism, and b) increasing dopamine release by stimulating exocytotic dopamine production. In summary, there is emerging and convincing evidence of MAO-inhibitors directly and indirectly increasing dopamine in both animal and human models.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested in agreement with others, that isatin may increase dopamine levels through greater availability of dopamine in the cytoplasmic reservoir ( Butcher et al, 1988 ; Justo et al, 2016 ). Isatin was further investigated by Faro et al (2021) who found that this MAO-inhibitor likely increases dopamine availability through a) suppression of dopamine metabolism, and b) increasing dopamine release by stimulating exocytotic dopamine production. In summary, there is emerging and convincing evidence of MAO-inhibitors directly and indirectly increasing dopamine in both animal and human models.…”
Section: Resultsmentioning
confidence: 99%